Investigating interactions of alpha-hydroxy acids with sodium benzoate for advanced formulation and translational applications: An ultrasonic approach - Ashpinder Kaur Gill; Nabaparna Chakraborty; K.C. Juglan (Chemical Physics Impact)
This study investigated the density and sound speed of ternary liquid systems (sodium benzoate + water +lactic acid/malic acid), using Anton Paar 5000 M at varying temperatures. Numerous volumetric and acoustical properties, including apparent molar volume, apparent specific volume, partial molar volume, transfer properties, apparent and partial molar isentropic compression, and thermal expansion coefficient were attained with the densities and sound speeds data. To provide a more comprehensive explanation for the findings, the co-sphere overlap concept examines the numerous interactions inside the liquid systems. The interactions between solutes and solvents in the ternary mixtures were characterized by calculating interaction coefficients. Ultrasonic techniques provide an innovative approach to studying the physico-chemical properties of liquids, offering insights into molecular interactions and structural behavior. By utilizing the molecular behavior of these widely used food and pharmaceutical additives, this research translates fundamental insights into practical innovations, creating new possibilities for advanced materials in healthcare and environmental sustainability, particularly in optimizing formulation stability, enhancing preservation efficiency, and improving product efficacy.